Transformasi Edukasi Nutrisi Melalui Digital Flipbook Sebagai Strategi Percepatan Penurunan Stunting Menuju SDGs 2030: Transforming Nutrition Education Through Digital Flipbooks as a Strategy to Accelerate Stunting Reduction Towards SDGs 2030 - Ika Nurfajriyani; Nessy Anggun Primasari; Elfa Dhela Miranda; Firdaus Firdaus; Eem Emasih Sumarni (LPPM STIKES Guna Bangsa Yogyakarta, 2026)
Background: Appropriate breastfeeding and complementary feeding practices are essential to prevent stunting, as inadequate nutritional intake increases the risk of growth impairment. Therefore, nutrition education needs to be strengthened to enable mothers to meet their children’s nutritional needs optimally, using easily accessible digital media such as flipbooks. Objective: To analyze the effectiveness of digital flipbook–based nutrition education on mothers’ perceptions of stunting prevention for children aged 0–60 months. Methods: A quantitative study with a pretest–posttest control group design. The sample consisted of 110 respondents selected through simple random sampling and divided into intervention and control groups. The study was conducted in the working area of Sukarahayu Primary Health Center, Subang. Results: There was a significant improvement in the intervention group after receiving the digital flipbook education (p = 0.0001), whereas the control group showed minimal changes (p = 0.012). Additionally, an Independent t-test showed a significant difference between the two groups in stunting prevention perception (t = 6.986; p = 0.000). Conclusion: The findings indicate that digital flipbook–based education positively influences mothers’ knowledge and perception regarding stunting prevention. Correlation analysis revealed that maternal age, education, income, and internet access were associated with improved perception of stunting prevention, while child’s sex, child’s age, mother’s occupation, and number of children were not associated. Thus, digital flipbooks can serve as a more effective educational alternative compared to traditional lecture methods in stunting prevention efforts.